PENCEGAHAN DEMENSIA PADA LANSIA MELALUI TERAPI BILABONG DI BANJAR PUCAK SARI DENPASAR UTARA - Ni Luh Diah Pradnya Kerthiari; Ni Putu Juliadewi Eka Gunawati; Ni Luh Gede Padma Peratiwi; Putu Ayu Sani Utami (Coping: Community of Publishing in Nursing, 2016)
Background: The elderly are more vulnerable to health problems due to a decline in physiological, cognitive and brain function, especially in the case of dementia. One therapy that can to cope with dementia is a brain exercise that consists of an adaptation of local culture through collaberation between drama gong (Bilabong) and Balinese gamelan. Objective: To prevent the incidence of dementia in the elderly with "Bilabong", increasing the willingness and ability of the elderly in participating in therapy and becoming an innovative program in Banjar Pucak Sari. Method: Dementia prevention can be done through community service by using “Bilabong” method that begins by defining the elderly who will follow brain gym activities, continued with manufacture of brain gym movements that combined “gamelan drama gong” as well as the implementation of activities. Results: After participation in the "Bilabong" program for 4 weeks there was a positive influence on stress levels , with a decrease in pre-test post-test significance (P = 0.000) of 25%. The participation rate of the elderly sample group was 100% and all participants were enthusiastic about the Bilabong. To ensure continuity, a Brain Gym training team will return to retrain the leaders of the Elderly association to 100% capacity. Conclusion: "Bilabong" Brain Gym Therapy exercises are activities incorporating Balinese gamelan accompaniment that serve to improve the knowledge of the elderly about how to prevent dementia, lower their stress levels, and innovation activities in Banjar Sari. Suggestion: Training and empowerment by the leader of elderly’s association and cadres will give a better impact in reducing the number of elderly dementia. Keywords: Bilabong, brain gym, dementia, drama gong, gamelan Bali.